Anti-icing / deicing coating based on micro / nano double-size SiO2 as well as preparation method and application of anti-icing / deicing coating
By combining dual-size SiO2 particles with MXene, a micro/nano-photothermal superhydrophobic coating was prepared, which solved the problem of ice covering and insufficient binding force of the existing coating in extreme weather, and achieved efficient and durable anti-icing/deicing effect and good binding force.
Patent Information
- Application Number
- CN202510394963.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-06-17
Smart Images

Figure CN120158186A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method of a superhydrophobic coating with anti-icing / de-icing ability, and specifically relates to an anti-icing / de-icing coating based on micro / nano dual-sized SiO2, its preparation method and application, belonging to the technical field of anti-icing / de-icing coatings. Background Art
[0002] The phenomena of snow accumulation and icing on the surface of cables may cause mechanical and electrical failures such as conductor galloping, wire breakage, collapse, and insulator flashover in the power system, bringing great harm to people's daily life and industrial production processes. At present, the main method for dealing with the icing problem of transmission lines in China is to remove the ice on the surface of transmission lines by manual or mechanical means after the occurrence of icing disasters to ensure the normal operation of transmission lines. This method is simple to operate, but has low efficiency, high cost, and dangerous operations. It is difficult for personnel to reach the scene in remote areas where long-distance transmission lines are located.
[0003] Constructing a superhydrophobic coating on the surface of cables, so that droplets are difficult to adhere to the cable surface and form ice accretion, is an anti-icing method with simple operation and low cost. It can be applied to large-area transmission line anti-icing and can endow the cable with long-term anti-icing ability. Therefore, it has received extensive attention in recent years. In recent years, researchers have found that there are many natural superhydrophobic surfaces in nature, and the most typical one is the lotus leaf surface. Li X et al. (Li X, Wang J, Yi G, et al. From waste plastic to artificial lotus leaf: Upcycling waste polypropylene to superhydrophobic spheres with hierarchical micro / nanostructure[J]. Applied Catalysis B: Environmental, 2024, 342: 123378.) prepared superhydrophobic spheres using polypropylene by referring to the lotus leaf surface; Jiang X et al. (Jiang X, Zhou C, Su J, et al. Enhanced anti-icing performance of novel superhydrophobic F-L@KH-SiO2 / OTMS coating synergistic preparation with bionic micro-nano structures and modified nanoparticles[J]. Chemical Engineering Journal, 2024, 498: 155264.) also prepared a superhydrophobic aluminum alloy surface through bionic microstructures with the help of femtosecond laser technology. However, these methods all require specific equipment for manufacturing, and the superhydrophobic properties have limitations.
[0004] To simplify the manufacturing process, Xie Z et al. (Xie Z, Wang H, Geng Y, et, al. Carbon-Based Photothermal Superhydrophobic Materials with Hierarchical StructureEnhances the Anti-Icing and Photothermal Deicing Properties[J]. ACS AppliedMaterials & Interfaces, 2021,13(40):48308-48321.) developed an efficient and durable photothermal superhydrophobic surface using electrochemical deposition and silanization. Zhu T et al. (Zhu T, Cheng Y, Huang J, et, al. Atransparent superhydrophobic coating with mechanochemical robustness foranti-icing, photocatalysis and self-cleaning[J]. Chemical EngineeringJournal, 2020,399:125746.) created a superhydrophobic coating with excellent anti-icing properties by combining heat treatment and spraying processes to form a hierarchical coating using polydimethylsiloxane (PDMS) nanoparticles and PDMS microparticles. However, engineering practices in recent years have shown that spraying superhydrophobic materials on the surface of cables cannot completely eliminate the problem of ice formation on the cable surface, and cables covered with hydrophobic coatings still have a certain probability of icing under extreme weather conditions. To make up for the deficiency of the anti-icing ability of superhydrophobic coatings, researchers have begun to try to load active deicing materials into hydrophobic coating materials to effectively solve the icing problem of cables under extreme weather conditions through an "anti-icing" + "deicing" integrated strategy. Photothermal deicing is a deicing method in which materials with photothermal conversion ability are added to the hydrophobic coating, and the coating can generate a high surface temperature under sunlight irradiation to quickly melt the ice crystals on the cable surface. Photothermal deicing has become a research hotspot in the field of anti-icing / deicing materials due to its advantages such as cleanliness and high efficiency.
[0005] In addition, the adhesion between the coating and the substrate is also an important factor affecting the coating performance. In practical applications, the coating needs to have strong adhesion to ensure that it will not peel off or fail under harsh environments. Traditional superhydrophobic coatings have deficiencies in adhesion and are prone to peeling under conditions such as mechanical friction and temperature changes, thus affecting the anti-icing / deicing performance of the coating. Summary of the Invention
[0006] In view of the icing problem of cables under extreme weather conditions, the present invention provides a method for preparing an anti-icing / de-icing coating based on micro / nano double-sized SiO2. By combining double-sized SiO2 particles and MXene, a micro / nano photothermal superhydrophobic coating is prepared, which solves the deficiencies of existing superhydrophobic coatings in anti-icing and de-icing capabilities and provides an efficient and durable anti-icing / de-icing method.
[0007] In order to enhance the robustness and durability of the superhydrophobic surface and extend its service life, the present invention is improved based on the Stober method, and a variety of nano-SiO2 particles are prepared. Silica SiO2 particles with different particle size dimensions are selected to improve the hydrophobic performance of the coating. Different from the existing single particle size system, micron-sized and nano-sized SiO2 particles are proposed. The double-sized SiO2 is doped in the PDMS / ER substrate to form a synergistic effect of micron particle skeleton support and nano particle surface modification, so as to effectively simulate the micro / nano hierarchical structure of the lotus leaf surface. This synergistic system of double-sized SiO2 particles can effectively promote the transformation of surface liquid beads from the Wenzel state to the Cassie state, making the contact angle of the coating surface reach the superhydrophobic critical point. Compared with the single particle size system, the hydrophobic performance of the coating is significantly improved and the ice adhesion strength on the coating surface is reduced. It effectively solves the surface energy gradient defect caused by particle agglomeration in the traditional hydrophobic coating, making the liquid droplets roll off naturally on the cable surface and it is difficult to form ice on the cable surface. The present invention innovatively introduces MXene into the cable anti-icing and de-icing system, constructs a dual-functional framework of a conductive network and a photothermal unit, reduces the overall resistance of the cable, and thus reduces the power loss during power transmission. As a material with good photothermal performance, the hydrophobic coating containing MXene can generate a high surface temperature in a short time under sunlight irradiation, so as to quickly melt a small amount of ice crystals (formed by the liquid that has not slipped off by itself) on the cable surface to make up for the deficiency of the superhydrophobic de-icing effect of the coating. At the same time, due to the synergistic effect of the double-sized SiO2 particles in the hydrophobic coating, the large-sized particles build a micron-scale rough skeleton of the substrate, providing structural support and enhancing the light scattering effect, while the small-sized nano particles fill the gaps in the skeleton, forming secondary nano-roughness and increasing the specific surface area. This micro-nano composite interface not only significantly improves the hydrophobic performance through the Cassie-Baxter effect, but its unique optical properties more effectively enhance the photothermal conversion efficiency through a multiple light reflection-absorption mechanism, achieving efficient light capture and energy conversion in a wide spectral range and improving the absorption efficiency of MXene for light. And due to the extremely low thermal conductivity of air, the air layer formed by the SiO2 particles can effectively reduce the heat conduction between the coating and the external environment, so that the coating can retain more heat. In addition, PDMS with excellent weather resistance is selected as the hydrophobic matrix of the superhydrophobic coating, and ER is doped to improve the mechanical properties of the superhydrophobic coating, making the superhydrophobic coating have good mechanical stability and weather resistance, and significantly improving the resistance to harsh environments. At the same time, a gradient sanding pretreatment process is adopted, and the surface of the aluminum substrate is polished with sandpaper to construct a three-dimensional anchoring structure on the aluminum substrate surface, breaking through the dependence of the traditional coating on chemical bond binding, and realizing the strong and tough binding of the coating and the substrate through the micro-mechanical anchoring effect, significantly improving the binding force between the superhydrophobic coating and the substrate.
[0008] An anti-icing / de-icing coating based on micro / nano dual-sized SiO2 provided by the present invention is prepared from the following components in parts by weight: Dual-sized SiO2: 2 - 6 parts, MXene: 2 - 6 parts, PDMS main agent and corresponding cross-linking agent: 1 - 2 parts, ER main agent and corresponding curing agent: 2 - 4 parts; Among them, micro-sized SiO2 accounts for 1 - 3 parts, and nano-sized SiO2 accounts for 1 - 3 parts.
[0009] In the present invention, PDMS is a two-component product purchased from Dow Corning Corporation, model: dc184; it includes a main agent and a corresponding cross-linking agent; ER is epoxy resin A and B glue purchased from Shenzhen Mingde Chemical Co., Ltd., including a main agent and a corresponding curing agent.
[0010] The present invention provides a preparation method for the above-mentioned anti-icing / de-icing coating based on micro / nano dual-sized SiO2, which includes the following steps: (1) Add Ti3AlC2 powder into a polytetrafluoroethylene container, and slowly drop HF into the polytetrafluoroethylene container. After the dropping is completed, place the polytetrafluoroethylene container in a constant temperature water bath for heat preservation; (2) After the heat preservation is completed, centrifuge the product obtained in step (1), and wash it repeatedly with deionized water. After drying, obtain MXene powder; (3) Mix tetraethyl orthosilicate and absolute ethanol in a beaker to obtain solution A; in another two beakers, mix ammonia water and deionized water according to different volume ratios to obtain solution B and solution C; (4) Slowly drop solution B into solution A for magnetic stirring, and slowly drop solution C into solution A for magnetic stirring, which are respectively used to prepare micro-sized SiO2 and nano-sized SiO2; (5) After the magnetic stirring is completed, perform centrifugal separation respectively, wash with deionized water and absolute ethanol, and after drying, obtain nano-sized SiO2 particles and micro-sized SiO2 particles.
[0011] (6) Add micro-sized SiO2 particles, nano-sized SiO2 particles and MXene obtained in step (2) into EA, and disperse the particles evenly in EA by ultrasonic treatment; (7) Add PDMS main agent and corresponding cross-linking agent, ER main agent and corresponding curing agent into the EA dispersion of MXene / SiO2, and perform magnetic stirring to completely dissolve PDMS and ER in the EA dispersion to obtain a dual-sized SiO2 / MXene coating solution; (8) Polish the surfaces of the substrate and the aluminum cable, and simultaneously clean the surface of the substrate with deionized water and ethanol. Then, dry the cleaned substrate for later use. (9) Use a spray gun to evenly spray the double-sized SiO2 / MXene coating solution obtained in step (7) onto the substrate, and after spraying, place the substrate in an oven to dry, obtaining a double-sized SiO2 / MXene photothermal superhydrophobic coating.
[0012] The above preparation method is further described as follows: In step (1), the dosage ratio of Ti3AlC2 powder to HF is 2 - 5 g∶10 - 15 mL, the temperature of the constant temperature water bath is 37 °C, and the heat preservation time is 24 h.
[0013] In step (2), the centrifuge speed is 3000 - 5000 rpm, the centrifugation time is 5 - 10 min, the number of times of washing with deionized water is 3 - 5 times, and the oven temperature is 50 - 80 °C.
[0014] In step (3), the volume ratio of tetraethyl orthosilicate to absolute ethanol in solution A is 1:2 - 3, the volume ratio of ammonia water to deionized water in solution B is 1:8 - 12, and the volume ratio of ammonia water to deionized water in solution C is 1:2 - 3.
[0015] In step (4), the volume ratio of solution A to solution B is 1:5 - 7, which is used to prepare micron-sized SiO2; the volume ratio of solution A to solution C is 1:4 - 6, which is used to prepare nano-sized SiO2; among them, the dropping speeds of solution B and solution C are both controlled at 5 - 10 mL / min, the magnetic stirring time after mixing solution B and solution A is 2 - 3 hours, and the magnetic stirring time after mixing solution C and solution A is 6 - 8 hours.
[0016] In step (5), the centrifuge speed is 3000 - 5000 rpm, the centrifugation time is 5 - 10 min, the number of times of washing with deionized water and absolute ethanol are 3 - 5 times respectively, and the drying temperature is 60 - 80 °C.
[0017] In step (6), the mass ratio of micron-sized SiO2 particles, nano-sized SiO2 particles and MXene is 0.3 - 0.6∶0.3 - 0.6∶0.6 - 1.2. In the dispersion liquid, every 100 mL of EA contains 6 - 12 g of solute (the solute is the total mass of SiO2 particles and MXene). The particle size of the micron-sized SiO2 powder is 0.5 - 1 μm, the particle size of the nano-sized SiO2 powder is 7 - 40 nm, and the ultrasonic time is 5 - 10 min. Preferably, the total amount of double-sized SiO2 and the mass ratio of PDMS is 1 - 2:1.
[0018] In step (7), the dosage of the PDMS base is as follows: in every 100 mL of the EA dispersion, there is 1 - 5 g of the PDMS base, and the mass ratio of the PDMS base to the crosslinking agent is 8 - 12:1. The dosage of the ER base is: in every 100 mL of the EA dispersion, there is 4 - 6 g of the ER base, and the mass ratio of the ER base to the curing agent is 2 - 4:1; the magnetic stirring speed is 500 - 600 rpm.
[0019] In step (8), the sandpaper used is 360 mesh, the number of times of cleaning with deionized water and ethanol is 3 - 5 times, and the drying temperature is 60 - 80 °C.
[0020] In step (9), the distance between the spray gun and the substrate is 10 - 15 cm, the spraying pressure of the spray gun is 15 - 20 psi, the spraying thickness of the coating is controlled within 100 - 200 μm, and the temperature of the oven used is 60 - 80 °C.
[0021] The present invention provides the application of the above-mentioned micro / nano photothermal superhydrophobic coating based on double-sized SiO2 in cable protection.
[0022] The beneficial effects of the present invention: (1) In this preparation method, by doping double-sized SiO2 into the PDMS / ER substrate, a synergistic effect of micron-particle skeleton support and nano-particle surface modification is formed, and a coating with a lotus-leaf-like micro / nano bionic structure is prepared. The air layer in the micro / nano structure can effectively promote the transformation of surface liquid beads from the Wenzel state to the Cassie state, making the contact angle of the cable coating surface reach the superhydrophobic critical point, and the droplets roll off naturally on the cable surface, thus it is difficult to form ice coating on the cable surface.
[0023] (2) The good photothermal conversion ability of MXene enables the coating to generate a relatively high surface temperature under sunlight irradiation, thereby quickly melting a small amount of ice crystals formed on the cable surface due to the liquid that has not slipped off by itself. Under the synergistic effect of superhydrophobic anti-icing and photothermal de-icing, problems such as cable breakage and short circuit caused by cable icing are effectively reduced; through the synergistic effect of superhydrophobic anti-icing - photothermal de-icing, it is effectively ensured that no ice coating can form on the cable surface, enabling the cable to operate normally under low-temperature conditions.
[0024] (3) MXene constructs a dual-functional framework of a conductive network and a photothermal unit, reducing the overall resistance of the cable, thereby reducing power loss during power transmission; the too-high insulation of the cable coating will cause the cable to be prone to breakage when struck by lightning. Adding MXene with good conductivity to the cable coating can effectively reduce the insulation of the cable coating, thereby effectively improving the lightning resistance of the cable, enabling the cable to operate better under extreme weather conditions.
[0025] (4) By optimizing the bonding method between the coating and the substrate and adopting a sanding pretreatment process, a three-dimensional anchoring structure is constructed on the surface of the aluminum substrate, breaking through the dependence of traditional coatings on chemical bond bonding, significantly improving the bonding strength between the superhydrophobic coating and the substrate, and ensuring that the coating has good stability and durability in harsh environments. Description of the Drawings
[0026] Figure 1 are SEM images of MXene powder, micron SiO2 (μ-SiO2) coating, micro / nano SiO2 coating (μ-n-SiO2), and MXene / μ-n-SiO2 coating under the conditions of Example 1; Figure 2 are the contact angle and rolling angle images of different coatings under the conditions of Example 1, where: (a), (d) are the contact angle images of different coatings; (b), (e) are the contact angle images of different addition amounts of double-sized SiO2; (c) is the rolling angle image of the MXene / μ-n-SiO2 coating; Figure 3 are the experimental results of the photothermal conversion ability of the MXene / μ-n-SiO2 coating under the conditions of Example 1: the surface temperature thermal imaging images of the MXene / μ-n-SiO2 coating under different intensities of simulated sunlight irradiation; Figure 4 are the experimental results of the photothermal conversion ability of the MXene / μ-n-SiO2 coating under the conditions of Example 1: the surface temperature rise of the MXene / μ-n-SiO2 coating under different intensities of simulated sunlight irradiation; Figure 5 are the experimental results of the change of the workpiece resistance with the surface temperature under the conditions of Example 1; where (a) is the surface temperature thermal imaging image of the workpiece under simulated sunlight irradiation; (b) is the change of the workpiece resistance and the surface temperature; Figure 6 are the experimental results of the anti-icing ability of the MXene / μ-n-SiO2 coating under the conditions of Example 1; where: (a) is the anti-icing ability result of the MXene / μ-n-SiO2 coating; (b) is the experimental result of the photothermal de-icing ability of the MXene / μ-n-SiO2 coating.
[0027] Figure 7 are the experimental results of the de-icing ability of the aluminum cable and the MXene / μ-n-SiO2 coating cable under the conditions of Example 1; where: (a) is the de-icing ability result of the aluminum cable; (b) is the experimental result of the de-icing ability of the MXene / μ-n-SiO2 coating cable. Detailed Description of the Invention
[0028] To better understand the present invention, the following further detailed description of the present invention will be given in conjunction with the accompanying drawings and embodiments. However, the scope of protection required by the present invention is not limited to the scope described in the following embodiments. Example 1
[0029] A preparation method of a micro / nano photothermal superhydrophobic coating based on double-sized SiO2 is provided. The preparation method is carried out according to the following steps: Step 1: Add 2 g of Ti3AlC2 powder into a polytetrafluoroethylene container, and slowly drop 10 mL of HF into the polytetrafluoroethylene container. After the dropping is completed, place the polytetrafluoroethylene container in a constant temperature water bath at 37 °C and keep it warm for 24 h.
[0030] Step 2: After the heat preservation is completed, centrifuge the product obtained in Step 1 at 3000 rpm for 10 min using a centrifuge, then wash it 3 times with deionized water, and place it in an oven at 50 °C to dry.
[0031] Step 3: Mix 4 mL of tetraethyl orthosilicate and 10 mL of absolute ethanol in a beaker to obtain Solution A; add 2 mL of ammonia water and 20 mL of deionized water to a beaker to mix and obtain Solution B; add 8 mL of ammonia water and 20 mL of deionized water to a beaker to mix and obtain Solution C.
[0032] Step 4: Take 4 mL of Solution A, slowly drop Solution B (the dropping rate is 10 mL / min) into 4 mL of Solution A and carry out magnetic stirring for 2 hours. Take another 7 mL of Solution A, slowly drop Solution C (the dropping rate is 8 mL / min) into 7 mL of Solution A and carry out magnetic stirring for 6 hours.
[0033] Step 5: After the magnetic stirring is completed, centrifuge the product obtained in Step 4 at 3000 rpm for 10 min using a centrifuge, wash it 3 times with deionized water and absolute ethanol respectively, and place it in an oven at 60 °C to dry.
[0034] Step 6: Add 0.3 g of SiO2 particles with a particle size of 0.5 μm, 0.3 g of SiO2 particles with a particle size of 20 nm, and 0.9 g of MXene obtained in Step 2 into 20 mL of EA, and ultrasonically treat for 10 min to uniformly disperse the powder in EA.
[0035] Step 7: Add 0.2 g of PDMS (PDMS: crosslinking agent = 10:1) and 0.8 g of ER (ER: curing agent = 3:1) to the EA dispersion of MXene / SiO2, and use a magnetic stirrer to stir at 600 rpm until PDMS, ER and the curing agent are completely dissolved.
[0036] Step 8: Polish the surfaces of the aluminum plate and the aluminum cable (using 360-mesh sandpaper), and at the same time, clean the surfaces of the aluminum plate and the aluminum cable 3 times with deionized water and ethanol. Subsequently, dry the cleaned aluminum plate in an oven at 60 °C.
[0037] Step 9: Use a spray gun to evenly spray the double-sized SiO2 / MXene coating solution obtained in Step 4 onto the aluminum plate and the aluminum cable under the conditions of maintaining a distance of 15 cm from the substrate and a pressure of 20 psi. After spraying, place the aluminum plate and the aluminum cable in an oven at 80 °C to dry, obtaining a double-sized SiO2 / MXene superhydrophobic coating.
[0038] Detect the microscopic morphology, hydrophobic performance, photothermal conversion performance, and anti-icing / de-icing ability of the MXene / μ-n-SiO2 coating prepared in the above examples. The experimental results are as shown Figures 1 to 6 below.
[0039] Figure 1 SEM images of MXene powder, μ-SiO2 coating, μ-n-SiO2, and MXene / μ-n-SiO2 coating. The SEM of MXene powder shows that Ti3AlC2 was successfully prepared into MXene with a lamellar structure after HF etching. The SEM image of the MXene / μ-n-SiO2 coating shows that the PDMS / ER dispersion containing MXene / μ-n-SiO2 forms a coating with a micron-scale structure on the cable surface (it can be seen from the enlarged view that the coating has a lotus-leaf-like micro / nano biomimetic structure), providing a basis for the superhydrophobic performance of the coating surface.
[0040] Figure 2The contact angle experimental results and the rolling angle experimental results of the MXene / μ-n-SiO2 superhydrophobic coating are shown. The experimental results show that the contact angle of the unmodified aluminum workpiece is 66.01°, showing hydrophilicity. The contact angles of the MXene / μ-SiO2 coating and the MXene / n-SiO2 coating are 125.05° and 140.47° respectively, indicating that only a limited hydrophobic ability can be obtained by coating the low surface energy material on the workpiece surface, and its contact angle cannot reach the superhydrophobic critical point (>150°). After adding MXene powder, μ-SiO2 powder and n-SiO2 powder into the matrix together, the micro / nano structure formed on the coating surface can quickly increase the contact angle of the coating to 160.12°, reaching the superhydrophobic critical point. The contact angle experimental results prove that the micro / nano structure of the MXene / μ-n-SiO2 coating can significantly improve the hydrophobic performance of the coating by storing a large amount of air. Subsequently, the workpiece was tilted, and a high-speed camera was used to record the rolling process of the droplet on the inclined workpiece plane to measure the rolling angle of the coating. The experimental results show that the droplet can freely roll on the surface of the MXene / μ-n-SiO2 coating with an inclination angle less than 1°, and the contact angle between the droplet and the inclined plane is greater than 150°, which also proves that the MXene / μ-n-SiO2 coating has good superhydrophobic ability.
[0041] Figure 3 and Figure 4 Figure shows the surface temperature change of the MXene / μ-n-SiO2 coating under simulated sunlight irradiation with different intensities. Sun in the figure refers to the light intensity; the experimental results show that the MXene / μ-n-SiO2 coating exhibits good photothermal performance after 160 s of simulated sunlight irradiation, and the surface temperature of the coating increases with the increase of the light intensity, enabling the MXene / μ-n-SiO2 coating to quickly melt the ice covering the coating surface under light conditions.
[0042] Figure 5 Figure shows the experimental results of the MXene / μ-n-SiO2 coating with the change of surface temperature. The results show that the increase in the coating temperature on the workpiece surface within the range of 100 °C causes a slight decrease in the workpiece resistance, proving that the photothermal effect of the coating will not hinder the power transmission of the cable.
[0043] Figure 6 (a) shows the anti-icing experimental results of the MXene / μ-n-SiO2 coating. The results show that flat ice particles that are difficult to remove are quickly formed on the surface of the aluminum workpiece, while ellipsoidal ice particles are formed on the surface of the MXene / μ-n-SiO2 coating and are very easy to remove under external force. Figure 6(b) shows the experimental results of the photothermal de-icing ability of the MXene / μ-n-SiO2 coating. The results show that the melting rate of ice particles on the surface of the MXene / μ-n-SiO2 coating is significantly higher than that of the aluminum plate, indicating that the MXene / μ-n-SiO2 coating has good photothermal de-icing ability.
[0044] Figure 7 (a) shows the experimental results of de-icing of the aluminum cable. The results show that after 20 minutes of illumination, the ice layer on the surface of the aluminum cable begins to melt, and until 25 minutes, a large amount of ice layer still adheres to the surface. Figure 7 (b) shows the experimental results of de-icing of the MXene / μ-n-SiO2 coated cable. The results show that the ice layer on the surface of the MXene / μ-n-SiO2 coated cable begins to melt only after 10 minutes, and the ice layer on the surface of the cable has completely melted at 20 minutes. The results show that the melting rate of the ice layer on the surface of the MXene / μ-n-SiO2 coated cable is significantly higher than that of the aluminum cable, indicating that the MXene / μ-n-SiO2 coating still has excellent photothermal de-icing ability on the cable. Example 2
[0045] A preparation method of a micro / nano photothermal superhydrophobic coating based on dual-sized SiO2 is provided, and this preparation method is carried out according to the following steps: Step 1: Add 4 g of Ti3AlC2 powder into a polytetrafluoroethylene container, and slowly drop 15 mL of HF into the polytetrafluoroethylene container. After the dropping is completed, place the polytetrafluoroethylene container in a constant temperature water bath at 35 °C for 24 h.
[0046] Step 2: After the heat preservation is completed, centrifuge the product obtained in Step 1 at 3000 rpm for 15 min using a centrifuge. After washing 4 times with deionized water, place it in an oven at 50 °C to dry.
[0047] Step 3: Mix 4 mL of tetraethyl orthosilicate and 8 mL of absolute ethanol in a beaker to obtain Solution A; add 2 mL of ammonia water and 18 mL of deionized water in a beaker to mix to obtain Solution B; add 8 mL of ammonia water and 16 mL of deionized water in a beaker to mix to obtain Solution C.
[0048] Step 4: Take 4 mL of Solution A, slowly drop Solution B (the dropping rate is 8 mL / min) into 4 mL of Solution A and stir magnetically for 3 hours. Take another 5 mL of Solution A, slowly drop Solution C (the dropping rate is 6 mL / min) into 5 mL of Solution A and stir magnetically for 8 hours.
[0049] Step 5: After the magnetic stirring is completed, centrifuge the product obtained in Step 4 at 3000 rpm for 10 min. After washing 3 times with deionized water and anhydrous ethanol respectively, place it in an oven at 80 °C for drying.
[0050] Step 6: Add 0.5 g of SiO2 particles with a particle size of 0.5 μm, 0.6 g of SiO2 particles with a particle size of 40 nm, and 1 g of MXene obtained in Step 2 to 20 mL of EA, and ultrasonically treat for 10 min to uniformly disperse the powder in EA.
[0051] Step 7: Add 0.4 g of PDMS (PDMS: crosslinking agent = 10:1) and 0.9 g of ER (ER: curing agent = 3:1) to the EA dispersion of MXene / SiO2, and use a magnetic stirrer to stir at 500 rpm until PDMS, ER, and the curing agent are completely dissolved.
[0052] Step 8: Polish the surfaces of the aluminum plate and the aluminum cable, and at the same time wash the surfaces of the aluminum plate and the aluminum cable 4 times with deionized water and ethanol. Subsequently, dry the washed aluminum plate in an oven at 60 °C.
[0053] Step 9: Use a spray gun to uniformly spray the double-sized SiO2 / MXene coating solution obtained in Step 4 on the aluminum plate and the aluminum cable under the conditions of maintaining a distance of 10 cm from the substrate and a pressure of 20 psi. After spraying, place the aluminum plate and the aluminum cable in an oven at 80 °C for drying to obtain a double-sized SiO2 / MXene superhydrophobic coating. Example 3
[0054] Provide a preparation method of a micro / nano photothermal superhydrophobic coating based on double-sized SiO2, and this preparation method is carried out according to the following steps: Step 1: Add 3 g of Ti3AlC2 powder to a polytetrafluoroethylene container, and slowly drip 10 mL of HF into the polytetrafluoroethylene container. After the dripping is completed, place the polytetrafluoroethylene container in a constant temperature water bath at 37 °C for heat preservation for 24 h.
[0055] Step 2: After the heat preservation is completed, centrifuge the product obtained in Step 1 at 3000 rpm for 10 min. After washing 3 times with deionized water, place it in an oven at 50 °C for drying.
[0056] Step 3: Mix 4 mL of tetraethyl orthosilicate and 10 mL of anhydrous ethanol in a beaker to obtain Solution A; add 2 mL of ammonia water and 24 mL of deionized water to the beaker to mix and obtain Solution B; add 8 mL of ammonia water and 24 mL of deionized water to the beaker to mix and obtain Solution C.
[0057] Step 4: Take 5 mL of Solution A, slowly add Solution B (the dropping rate is 6 mL / min) to 5 mL of Solution A and conduct magnetic stirring for 2 hours. Separately, take 6 mL of Solution A, slowly add Solution C (the dropping rate is 10 mL / min) to 6 mL of Solution A and conduct magnetic stirring for 8 hours.
[0058] Step 5: After the magnetic stirring is completed, centrifuge the product obtained in Step 4 at 3000 rpm for 10 min. After washing 3 times with deionized water and anhydrous ethanol respectively, place it in an oven at 60 °C for drying.
[0059] Step 6: Add 0.3 g of SiO2 particles with a particle size of 0.5 μm, 0.4 g of SiO2 particles with a particle size of 30 nm, and 1.2 g of MXene obtained in Step 2 to 20 mL of EA, and ultrasonically treat for 5 min to uniformly disperse the powder in EA.
[0060] Step 7: Add 0.3 g of PDMS (PDMS: cross-linking agent = 10:1) and 0.7 g of ER (ER: curing agent = 3:1) to the EA dispersion of MXene / SiO2, and use a magnetic stirrer to stir at 600 rpm until PDMS, ER, and the curing agent are completely dissolved.
[0061] Step 8: Polish the surfaces of the aluminum plate and the aluminum cable, and at the same time wash the surfaces of the aluminum plate and the aluminum cable 3 times with deionized water and ethanol. Subsequently, dry the washed aluminum plate in an oven at 60 °C.
[0062] Step 9: Use a spray gun to uniformly spray the double-sized SiO2 / MXene coating solution obtained in Step 4 on the aluminum plate and the aluminum cable under the conditions of maintaining a distance of 12 cm from the substrate and a pressure of 15 psi. After spraying, place the aluminum plate and the aluminum cable in an oven at 60 °C for drying to obtain a double-sized SiO2 / MXene superhydrophobic coating.
Claims
1. An anti-icing / de-icing coating based on micro / nano dual-size SiO2, characterized in that: The composition comprises the following components in parts by weight: Double size SiO2: 2-6 parts, MXene: 2-6 parts, PDMS main agent and corresponding cross-linking agent: 1-2 parts, ER main agent and corresponding curing agent: 2-4 parts; Among them, micron-sized SiO2 accounts for 1-3 parts, and nano-sized SiO2 accounts for 1-3 parts.
2. A method for preparing an anti-icing / de-icing coating based on micro / nano dual-size SiO2 according to claim 1, characterized in that The following steps are involved: (1) Add Ti3AlC2 powder into a polytetrafluoroethylene container, and slowly drop HF into the polytetrafluoroethylene container. After the dropwise addition is completed, place the polytetrafluoroethylene container in a constant temperature water bath to keep it warm; (2) After the insulation is completed, the product obtained in step (1) is centrifuged using a centrifuge, and repeatedly washed with deionized water, and then dried to obtain MXene powder; (3) In a beaker, tetraethyl orthosilicate and anhydrous ethanol are mixed to obtain solution A; in two other beakers, ammonia water and deionized water are mixed in different volume ratios to obtain solutions B and C; (4) slowly adding solution B dropwise into solution A and magnetically stirring, and slowly adding solution C dropwise into solution A and magnetically stirring, to prepare micron-sized SiO2 and nano-sized SiO2, respectively; (5) After the magnetic stirring is completed, centrifugal separation is performed, and deionized water and anhydrous ethanol are used for washing, and then drying is performed to obtain nano-scale SiO2 particles and micron-scale SiO2 particles; (6) adding micrometer-sized SiO2 particles, nanometer-sized SiO2 particles and the MXene obtained in step (2) into EA, and uniformly dispersing the particles in EA by ultrasonic treatment; (7) Add PDMS main agent and corresponding crosslinking agent, ER main agent and corresponding curing agent to the EA dispersion of MXene / SiO2, and stir magnetically to completely dissolve PDMS and ER in the EA dispersion to obtain a dual-size SiO2 / MXene coating solution; (8) Grinding the surface of the substrate, cleaning the surface of the substrate with deionized water and ethanol, and then drying the cleaned substrate for later use; (9) Use a spray gun to evenly spray the dual-sized SiO2 / MXene coating solution obtained in step (7) on the substrate, and after spraying, place the substrate in an oven to dry to obtain a dual-sized SiO2 / MXene photothermal super hydrophobic coating.
3. The method for preparing the anti-icing / de-icing coating based on micro / nano dual-size SiO2 according to claim 2, characterized in that: In step (1), the dosage ratio of Ti3AlC2 powder to HF is 2-5 g: 10-15 mL, the temperature of the constant temperature water bath is 37°C, and the insulation time is 24 h; in step (2), the centrifuge speed is 3000-5000 rpm, the centrifugation time is 5-10 min, the number of deionized water washings is 3-5 times, and the oven temperature is 50-80°C.
4. The method for preparing an anti-icing / de-icing coating based on micro / nano dual-size SiO2 according to claim 2, characterized in that: In step (3), the volume ratio of ethyl orthosilicate to anhydrous ethanol in solution A is 1:2-3, the volume ratio of ammonia water to deionized water in solution B is 1:8-12, and the volume ratio of ammonia water to deionized water in solution C is 1:2-3.
5. The method for preparing an anti-icing / de-icing coating based on micro / nano dual-size SiO2 according to claim 2, characterized in that: In step (4), the volume ratio of solution A to solution B is 1:5-7, which is used to prepare micron-sized SiO2; the volume ratio of solution A to solution C is 1:4-6, which is used to prepare nano-sized SiO2; wherein the dropping speeds of solution B and solution C are both controlled at 5-10 mL / min, the magnetic stirring time after solution B and solution A are mixed is 2-3 hours, and the magnetic stirring time after solution C and solution A are mixed is 6-8 hours.
6. The method for preparing an anti-icing / de-icing coating based on micro / nano dual-size SiO2 according to claim 2, characterized in that: In step (5), the centrifuge speed is 3000-5000 rpm, the centrifugation time is 5-10 min, the number of washing with deionized water and anhydrous ethanol is 3-5 times respectively, and the drying temperature is 60-80 °C.
7. The method for preparing an anti-icing / de-icing coating based on micro / nano dual-size SiO2 according to claim 2, characterized in that: In step (6), the mass ratio of micron-sized SiO2 particles, nano-sized SiO2 particles and MXene is 0.3-0.6:0.3-0.6:0.6-1.2, the dispersion contains 6-12 g of solute per 100 mL of EA, the particle size of the micron-sized SiO2 powder is 0.5-1 μm, the particle size of the nano-sized SiO2 powder is 7-40 nm, and the ultrasonic time is 5-10 min.
8. The method for preparing an anti-icing / de-icing coating based on micro / nano dual-size SiO2 according to claim 2, characterized in that: The amount of PDMS main agent used in step (7) is: 1-5 g PDMS main agent per 100 mL EA dispersion, and the mass ratio of PDMS main agent to cross-linking agent is 8-12:1; the amount of ER main agent used is: 4-6 g ER main agent per 100 mL EA dispersion, and the mass ratio of ER main agent to curing agent is 2-4:1; the magnetic stirring speed is 500-600 rpm.
9. The method for preparing an anti-icing / de-icing coating based on micro / nano dual-size SiO2 according to claim 2, characterized in that: The sandpaper used in step (8) is 360 mesh, the number of cleaning times with deionized water and ethanol is 3-5 times, and the drying temperature is 60-80°C; in step (9), the distance between the spray gun and the substrate is 10-15 cm, the spray gun spraying pressure is 15-20 psi, the coating spraying thickness is controlled at 100-200 μm, and the oven temperature used is 60-80°C; the substrate is an aluminum plate or an aluminum cable.
10. Use of the anti-icing / de-icing coating based on micro / nano dual-size SiO2 as claimed in claim 1 in cable protection.
Citation Information
Cited By
Multi-component high-strength anti-icing material as well as preparation method and application thereof
CN121896857A